PENGARUH PROGRAM PENGEMBANGAN DAN PELATIHAN, WORK EXPERIENCE, DAN KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KOMPETENSI PEGAWAI DAN KINERJA PEGAWAI (Peran Motivasi Sebagai Variabel Moderasi) - Aditya Burhan; Pujiharti Pujiharti; Dian Meinalisa (Riset Manajemen dan Akuntansi, 2022)
The basis for this assessment was to determine whether the development, training, drawing experience, and asset management of small variables influenced employee skills, employee performance, and motivation. The technology used in this experiment is digital. Structural equation modeling (SEM) is used in analytical techniques. 150 employees were involved in the audit. The results of this assessment are as follows. 1) Development and training programs have a significant impact on employee productivity, 2) Development and training improve employee performance, 3) Development and training programs improve employee efficiency, 4) Work experience improves employee efficiency, 5). Change there is no leadership, affects employee productivity, 6) Change leadership affects a company's employee performance, 7) Employee efficiency improves a company's employee performance, 8) Motivation affects employee performance.